Strategi Kepala Madrasah Dalam Meningkatkan Kompetensi Sosial Guru di MA Mambaus Sholihin Gresik - Hidayatul Mufidah (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2023)
MA Mambaus Sholihin Gresik is an institution located in the village of suci gresik which is not far from residential areas. This madrasah is a basic educational institution under the auspices of the MA Mambaus Sholihin Gresik foundation. This educational institution has enough good quality so that the parents of students send their children to that institution. Along with the intense educational competition. No wonder parents want the best for their children. The teachers at this madrasa also have good communication with the surrounding community. Then do this research. This study aims to answer several problem formulations; 1) What is the strategy of the madrasa head in improving the social competence of teachers?, 2) What are the supporting and inhibiting factors for the head of the madrasa in improving the social competence of teachers? This type of research includes qualitative research, which produces data and is analyzed using a descriptive method that is adapted to the social competence of teachers at MA Mambaus Sholihin Gresik. Data collected using interview techniques, observation and documentation. The results of this study are that the principal's strategy in improving the social competence of teachers at MA Mambaus Sholihin Gresik is to create a sense of togetherness by increasing good, intimate and open communication with fellow teachers, students and the community. And the head of the madrasa also applies the 3S attitude, namely smiling, greeting and greeting. The strategies used by the madrasa head in improving the social competence of teachers at MA Mambaus Sholihin Gresik are as follows: a) fostering teacher discipline, b) providing motivation, c) upgrading and workshops, d) supervision, e) fostering teacher creativity. And indirectly the madrasa head has carried out his strategy properly and according to the strategic steps in improving the social competence of teachers. As for the results of this research, it is suggested that in the future in carrying out their duties as the highest leadership in an institution, a school principal is expected to be more optimal in increasing the social competence of teachers. because in fact the strategy used by the head of the madrasa is less specific and refers too much to the community. And the madrasa head should further improve his communication with teachers, students and the surrounding community. To make it easier to make improvements regarding the social competence of teachers.